A study in four European countries to examine the importance of sensory attributes of oral nutritional supplements on preference and likelihood of compliance - Tahsin Gökçem ÖZÇAĞLI; Janet STELLING; Julia STANFORD (Turkish Journal of Gastroenterology, 2019)
-